Comparison of the biomarkers for targeted therapies in primary extra-mammary and mammary Paget's disease - Gatalica, Zoran; Vranic, Semir; Krušlin, Božo; Poorman, Kelsey; Stafford, Phillip; Kacerovska, Denisa; Senarathne, Wijendra; Florento, Elena; Contreras, Elma; Leary, Alexandra; Choi, April; In, Gino K (Cancer medicine, 2020)
BACKGROUND: Primary Extra-mammary Paget's disease (EMPD) is a very rare cutaneous adenocarcinoma affecting anogenital or axillary regions. It is characterized by a prolonged course with recurrences and eventually distant metastatic spread for which no specific therapy is known. METHODS: Eighteen EMPD (13 vulvar and five scrotal) and ten mammary Paget's disease (MPD) cases were comprehensively profiled for gene mutations, fusions and copy number alterations, and for therapy-relevant protein biomarkers). RESULTS: Mutations in TP53 and PIK3CA were the most frequent in both cohorts: 7/15 and 5/15 in EMPD; 1/6 and 4/7 in MPD HER2 gene amplification was detected in 4/18 EMPD (3 vulvar and 1 scrotal case) in contrast to MPD where it was detected in the majority (7/8) of cases. TOP2A gene amplification was seen in 2/12 EMPD and 1/6 MPD, respectively. Similarly, no difference in estrogen receptor expression was seen between the EMPD (4/15) and MPD (3/10). Androgen receptor was also expressed in the majority of both cohorts (12/16 EMPD) and (7/8 MPD).Here ARv7 splice variant was detected in 1/7 EMPD and 1/4 MPD cases, respectively. PD-L1 expression on immune cells was exclusively observed in three vulvar EMPD. In contrast to MPD, six EMPDs harbored a "high" tumor mutation burden (≥10 mutations/Mb). All tested cases from both cohorts were MSI stable. CONCLUSIONS: EMPD shares some targetable biomarkers with its mammary counterpart (steroid receptors, PIK3CA signaling pathways, TOP2A amplification). HER2 positivity is notably lower in EMPD while biomarkers to immune checkpoint inhibitors (high TMB and PD-L1) were observed in some EMPD. Given that no consistent molecular alteration characterizes EMPD, comprehensive theranostic profiling is required to identify individual patients with targetable molecular alterations.
Keywords: Scrotum; Aged; Aged, 80 and over; Breast; Precision Medicine; Retrospective Studies; Sequence Analysis, DNA; lidé středního věku; senioři; nádory kůže; Biomarkers, Tumor; nádory prsu; lidé; sekvenční analýza DNA; Adult; Antineoplastic Combined Chemotherapy Protocols; Middle Aged; Breast Neoplasms; vulva; dospělí; Microsatellite Instability; amplifikace genu; nádorové biomarkery; skrotum; Female; Mutation; Paget's Disease, Mammary; Skin Neoplasms; Skin; Molecular Targeted Therapy; senioři nad 80 let; individualizovaná medicína; mutace; Male; protokoly protinádorové kombinované chemoterapie; ženské pohlaví; mikrosatelitní nestabilita; variabilita počtu kopií segmentů DNA; prsy; Gene Amplification; mužské pohlaví; Humans; Pagetova nemoc prsu; kůže; cílená molekulární terapie; Paget Disease, Extramammary; extramamární Pagetova nemoc; Vulva; DNA Copy Number Variations; retrospektivní studie